CHIP-mediated degradation and DNA damage-dependent stabilization regulate base excision repair proteins. - Parsons, J; Tait, P; Finch, D; Dianova, I; Allinson, S; Dianov, G (2008)
Base excision repair (BER) is the major pathway for processing of simple lesions in DNA, including single-strand breaks, base damage, and base loss. The scaffold protein XRCC1, DNA polymerase beta, and DNA ligase IIIalpha play pivotal roles in BER. Although all these enzymes are essential for development, their cellular levels must be tightly regulated because increased amounts of BER enzymes lead to elevated mutagenesis and genetic instability and are frequently found in cancer cells. Here we report that BER enzyme levels are linked to and controlled by the level of DNA lesions. We demonstrate that stability of BER enzymes increases after formation of a repair complex on damaged DNA and that proteins not involved in a repair complex are ubiquitylated by the E3 ubiquitin ligase CHIP and subsequently rapidly degraded. These data identify a molecular mechanism controlling cellular levels of BER enzymes and correspondingly the efficiency and capacity of BER.